Trash E-Gone / Nur Qursya Mohd Noor Salizan - Mohd Noor Salizan, Nur Qursya (2020)
Our company has a new product to introduce to consumers which is the smart waste bin named Trash E-Gone. Our company is targeting to supply a high technology waste bin when there is no suitable method to manage the waste disposal activities. Apart from that, a foul smell from the rotten wastes that remain untreated for a long time may cause disturbance to the surroundings and lead to long-term problems. Trash E-Gone is a specialized waste bin that are environmental-friendly. The technologies invented such as to produce waste bin with a solar powered attached on the lid as solar power will generate light energy received from the sun to minimize the waste in the waste bin by decomposing the waste to 50% lesser. Trash E-Gone are also consist of a compressor in order to squash or compress the solid waste that tend to maximized the space in the bins. Moreover, Trash E-Gone are covered with activated carbon fillers to eliminate or reduce the stinky smell and the presence of automatic disinfectants spray to eliminate microbial pathogens. The overall marketing strategy will be included in specific marketing philosophy and strategy of the company. Firstly, our target market would be trading company in Malaysia especially within Selangor area. The next target customers are individual customers or direct buyer specifically lived in Kota Damansara, Petaling Jaya areas or within Selangor. The objective of this products is to promote the trend of environmental-friendly product to preserve our environment. It comprises varieties of goods and services, which engaged the surrounding area with minimum or no harm to the environment. In the other words, eco-friendly product gives a positive impact to our environment and future generation.